Current Research of the Human Resources Information Systems – Systematic Literature Review - Martin POLIVKA; Lilia DVORAKOVA (Communications of International Proceedings, 2021)
The aim of the paper is to assess the current state of research in the field of human resources information systems, with a special focus on the influence of the technologies of the so-called fourth industrial revolution on such systems. Given the fact that the technologies of the fourth industrial revolution were originally related mainly to the field of manufacturing and logistic processes, it can be presumed that their reflection in the field of human resources will be rather delayed. Methodology consisting of six successive steps was chosen to identify, classify and analyse professional papers dealing with the topic of human resources information systems published in last five years. As for the content of the chosen papers, five main topics and nineteen subtopics were identified. Technologies of the fourth industrial revolution were not mentioned very frequently in the analysed papers. The current trend of web-based systems hosted in the cloud occurred for most of them, followed by the big data phenomenon. Nevertheless, the analysis conducted proves that the technologies of the fourth industrial revolution are, as presumed, not the most crucial topic in the current discussion about the human resources information systems and that there exists a remarkable research gap in this field, which can be filled in by further studies.
Keywords: Industry4.0; HRIS; Human resources information systems